Molecular characteristics and chromatin texture features in acute promyelocytic leukemia - De Mello Mariana R B; Albuquerque Dulcineia M; Pereira-Cunha Fernanda; Albanez Krizzia B; Pagnano Katia B B; Costa Fernando F; Metze Konradin; Lorand-Metze Irene (BMC, 2012)
Abstract Background Acute promyelocytic leukemia is a cytogenetically well defined entity. Nevertheless, some features observed at diagnosis are related to a worse outcome of the patients. Methods In a prospective study, we analyzed peripheral (PB) leukocyte count, immunophenotype, methylation status of CDKN2B, CDKN2A and TP73; FLT3 and NPM1 mutations besides nuclear chromatin texture characteristics of the leukemic cells. We also examined the relation of these features with patient's outcome. Results Among 19 cases, 4 had a microgranular morphology, 7 presented PB leukocytes >10x109/l, 2 had FLT3-ITD and 3 had FLT3-TKD (all three presenting a methylated CDKN2B). NPM1 mutation was not observed. PB leukocyte count showed an inverse relation with standard deviation of gray levels, contrast, cluster prominence, and chromatin fractal dimension (FD). Cases with FLT3-ITD presented a microgranular morphology, PB leukocytosis and expression of HLA-DR, CD34 and CD11b. Concerning nuclear chromatin texture variables, these cases had a lower entropy, contrast, cluster prominence and FD, but higher local homogeneity, and R245, in keeping with more homogeneously distributed chromatin. In the univariate Cox analysis, a higher leukocyte count, FLT3-ITD mutation, microgranular morphology, methylation of CDKN2B, besides a higher local homogeneity of nuclear chromatin, a lower chromatin entropy and FD were associated to a worse outcome. All these features lost significance when the cases were stratified for FLT3-ITD mutation. Methylation status of CDNK2A and TP73 showed no relation to patient's survival. Conclusion in APL, patients with FLT3-ITD mutation show different clinical characteristics and have blasts with a more homogeneous chromatin texture. Texture analysis demonstrated that FLTD-ITD was accompanied not only by different cytoplasmic features, but also by a change in chromatin structure in routine cytologic preparations. Yet we were not able to detect chromatin changes by nuclear texture analysis of patients with the FTLD-TKD or methylation of specific genes.